Perhitungan Volume Stockpile dan Pengoptimalan Waktu Pengolahan Stockpile 3, 5 dan 6 Terhadap Produksi Alat Gali muat dan Alat Angkut pada TB Primer Batubesi PT Timah Tbk - Neni Sherina; Franto Franto; Mardiah Mardiah (MINERAL, 2023)
PT Timah Tbk's Batubesi Primary Large Mine has experienced a significant decline in production in recent years, causing a change in the mining process to stockpile management that is still economical with a grade of 0.2%. This study aims to determine the volume and production of stockpiles 3, 5 and 6, the type of sediment and Sn content of stockpile material and the time required to spend stockpile material 3, 5 and 6 in order to get the optimal time. The method used is a quantitative method by taking cycle time data as much as 30 data and analyzing sample levels using XRF on each stockpile. The results of this study obtained the volume of stockpile 3 material is 132,648.42 m3,, stockpile 5 is 162,570.25 m3, and stockpile 6 is 33,090.19 m3. The calculated machine productivity at stockpile 3 is 42.17 tons/hour, stockpile 5 is 48.11 tons/hour and stockpile 6 is 39.53 tons/hour. The highest Sn content is found in stockpile 6 which is 0.33% with the type of skarn sediment. While the lowest Sn content is found in stockpile 3 which is 0.2% with oxide clay sediment type. In stockpile 5, the Sn content is 0.31% with the type of oxide clay sediment. The remaining volume of stockpile material in stockpiles 3, 5 and 6 can be spent with a time of 2.78 years using 1 unit of excavation equipment and 1 unit of transportation equipment. Optimization is carried out so that the remaining stockpile reserves can be spent within 1.74 years using 1 unit of excavation equipment and 2 units of transport equipment.